2014
DOI: 10.1371/journal.pone.0112694
|View full text |Cite
|
Sign up to set email alerts
|

Behavioral Responses to Mammalian Blood Odor and a Blood Odor Component in Four Species of Large Carnivores

Abstract: Only little is known about whether single volatile compounds are as efficient in eliciting behavioral responses in animals as the whole complex mixture of a behaviorally relevant odor. Recent studies analysing the composition of volatiles in mammalian blood, an important prey-associated odor stimulus for predators, found the odorant trans-4,5-epoxy-(E)-2-decenal to evoke a typical “metallic, blood-like” odor quality in humans. We therefore assessed the behavior of captive Asian wild dogs (Cuon alpinus), Africa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
36
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 33 publications
2
36
0
Order By: Relevance
“…Further elution with hexane/EtOAc (30:1) gave 80 mg (3%) of (2E,4R * ,5R * )-(±)-1. Its IR, 1 H NMR and MS spectra were identical with those described for (±)-1 in Section 4.5. Further elution with hexane/EtOAc (10:1-4:1) gave 1.09 g of unidentified polar materials.…”
Section: Generalmentioning
confidence: 69%
See 1 more Smart Citation
“…Further elution with hexane/EtOAc (30:1) gave 80 mg (3%) of (2E,4R * ,5R * )-(±)-1. Its IR, 1 H NMR and MS spectra were identical with those described for (±)-1 in Section 4.5. Further elution with hexane/EtOAc (10:1-4:1) gave 1.09 g of unidentified polar materials.…”
Section: Generalmentioning
confidence: 69%
“…1) could be as efficient in eliciting behavioral responses among dogs and tigers as the odor of mammalian blood. 1 The fact that the metallic blood smell of 1 attracts predators is of interest in its ecological context to study the chemistry of how carnivores find their prey. 2 Nilsson et al, however, examined only racemic 1, which had been known since 1991 as one of the primary odorants in wheat bread crumb 3 and popcorn 4 by Schieberle et al Aldehyde 1 was found in many other food systems 5 such as black tea, 6 and its biogenetic pathway was speculated.…”
Section: Introductionmentioning
confidence: 99%
“…As one of the mammalian prey species, dogs may have been more sensitive to a human odor compared to non‐prey‐associated odors (Nilsson et al . ). Furthermore, the interaction between certain genotypes and a certain odor was found for the OR10H1‐like: c.632C>T, OR10H1‐like: c.770A>T, OR4C11‐like: c.511T>G and OR4C11‐like: c.692G>A loci ( P < 0.01) (Table S6).…”
Section: Genetic Polymorphism Analysis Of Snpsmentioning
confidence: 97%
“…(6R,7S,2E)-6,7-Epoxy-2-nonenal has been identified as a sex-aggregation pheromone of the red-necked longhorn beetle (Aromia bungii) [5] and its synthesis has been recently developed by Mori and co-workers [6,7]. (2E)-trans-4,5-Epoxy-2-decenal is present in mammalian blood and may be used by predators to track their prey [8,9]. A classical example of cis-epoxides with semiochemical activity is the chemical communication system of the gypsy moth (Lymantria dispar) and the nun moth (Lymantria monacha).…”
Section: Synthesis Of Disparlure and Monachalure Enantiomers From 23mentioning
confidence: 99%